Pharmacognostical study of Damanak - Artemisia nilagirica (C.B CLARKE) Pamp.) (International Journal of Ayurveda and Pharma Research, 2025)
Damanak- Artemisia nilagirica is a tall, aromatic, pubescent or villous shrub-like herb found throughout India's hilly regions. The plant has been mentioned in various Nighantu about its use as Hrudya, Vrushya, Grahani, Visha, Kustha, Kleda, Kandu and in Tridosha (disease of all the three Doshas). There are many ethnobotanical uses which indicates this herb should be studied more extensively to confirm these results and reveal other potential therapeutic effects. Davana oil has a deep, mellow, persistent rich fruity odour. Oil of Davana is used in expensive perfume compositions. It is understood that the oil is also being used for flavouring cakes and pastries. This also marks the use of Damanak as commercial plant. The present article intends to study the plant for its pharmacognosy and to know its therapeutic uses mentioned in various Nighantu.